MEREK SEBAGAI ALAT KOMUNIKASI PEMASARAN: Implementasi UU Nomor 15 Tahun 2001 tentang Merek (Fokus Ekonomi, 2009)
The brand has become a central issue in product strategy. In this competitive condition, it plays an important role. It also facilitates the management due to its identity to which it adheres. When brand has been patented hence company will get protection of law from other party effort which will take illegal benefit. With the brand, company will be able to build its prefered image, thereby having a strong competitive advantage.